Contrastive Learning for Image Registration in Visual Teach and Repeat Navigation - Rozsypálek, Zdeněk; Broughton, George; Linder, Pavel; Rouček, Tomáš; Blaha, Jan; Mentzl, Leonard; Kusumam, Keerthy; Krajník, Tomáš (Sensors (Basel, Switzerland), 2022)
Visual teach and repeat navigation (VT&R) is popular in robotics thanks to its simplicity and versatility. It enables mobile robots equipped with a camera to traverse learned paths without the need to create globally consistent metric maps. Although teach and repeat frameworks have been reported to be relatively robust to changing environments, they still struggle with day-to-night and seasonal changes. This paper aims to find the horizontal displacement between prerecorded and currently perceived images required to steer a robot towards the previously traversed path. We employ a fully convolutional neural network to obtain dense representations of the images that are robust to changes in the environment and variations in illumination. The proposed model achieves state-of-the-art performance on multiple datasets with seasonal and day/night variations. In addition, our experiments show that it is possible to use the model to generate additional training examples that can be used to further improve the original model's robustness. We also conducted a real-world experiment on a mobile robot to demonstrate the suitability of our method for VT&R.
Keywords: Robotics; neuronové sítě; image representations; visual teach and repeat navigation; machine learning; Neural Networks, Computer; contrastive learning; long-term autonomy; robotika